On curvatures of a frenet curve in the pseudo - Galilean space G31 - Ö?renmiş, Alper Osman (My University, 2010)
In this paper, we study curvatures of a frenet curve in the pseudo-Galilean space and we obtain some characterizations. © 2010 Academic Journals.
Keywords: Curvature; Frenet curve; Pseudo-galilean space